Upregulation of Znf179 acetylation by SAHA protects cells against oxidative stress - Wu, Chung-Che (Redox Biol, 2018)
The accumulation of reactive oxygen species (ROS) commonly occurs during normal aging and during some acute/chronic progressive disorders. In order to avoid oxidative damage, scavenging of these radicals is important. Previously, we identified zinc finger protein 179 (Znf179) as a neuroprotector that increases antioxidant enzymes against superoxide radicals. However, the molecular mechanisms involved in the activation and regulation of Znf179 remain unresolved. Here, by performing sequence alignment, bioinformatics analysis, immunoprecipitation using two specific acetyl-lysine antibodies, and treatment with the histone deacetylase (HDAC) inhibitor SAHA, we determined the lysine-specific acetylation of Znf179. Furthermore, we investigated Znf179 interaction with HDACs and revealed that peroxide insult induced a dissociation of Znf179-HDAC1/HDAC6, causing an increase in Znf179 acetylation. Importantly, HDAC inhibition by SAHA further prompted Znf179 hyperacetylation, which promoted Znf179 to form a transcriptional complex with Sp1 and increased antioxidant gene expression against oxidative attack. In summary, the results obtained in this study showed that Znf179 was regulated by HDACs and that Znf179 acetylation was a critical mechanism in the induction of antioxidant defense systems. Additionally, HDAC inhibitors may have therapeutic potential for induction of Znf179 acetylation, strengthening the Znf179 protective functions against neurodegenerative processes.